Imaging of Skeletal Metastases in Myxoid Liposarcoma. (30th March 2010) - Noble, J. L.; Moskovic, E.; Fisher, C.; Judson, I.
Abstract : Unlike other soft tissue sarcomas, myxoid/round cell liposarcoma (MRCL) has a tendency to spread to extrapulmonary sites but bone metastases are thought to be uncommon. In case reports, negative bone scintigraphy has been noted in patients with myxoid/round cell liposarcoma and bone metastases but the prevalence and optimal method of diagnosis of bone metastases in this common subtype of liposarcoma are unclear. In an attempt to answer these questions, data were obtained from a prospective database of patients with sarcoma, including MRCL, and the diagnostic imaging used was examined. A variety of imaging tools were used including plain X-rays, bone scintigraphy, computed tomography (CT), and magnetic resonance imaging (MRI). Eight patients (4.3%) developed skeletal metastases all of which were positive on MRI. Bone scintigraphy was negative in two out of four cases, CT was negative in six out of seven, and X-rays were negative in four. Radiography and CT measure mainly cortical bone involvement, whereas MRI examines bone marrow. When investigating patients with MRCL for bone pain, negative X-rays and bone scans do not rule out bone metastases. In our experience, MRI provides the most sensitive technique for the diagnosis of bone metastases in MRCL.